2001
DOI: 10.1108/00368790110366398
|View full text |Cite
|
Sign up to set email alerts
|

Advancements of tribological performance of carbon brushes in electrical motors

Abstract: Access to this document was granted through an Emerald subscription provided by emerald-srm:368933 [] For AuthorsIf you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and practice to the be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 2 publications
(1 reference statement)
0
4
0
Order By: Relevance
“…To assure a low level of mechanical wear, the formation of a stable friction layer on the contacting surface is of vital importance [9]. This friction layer increases the real contact area and decreases friction, temperature and arcing.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…To assure a low level of mechanical wear, the formation of a stable friction layer on the contacting surface is of vital importance [9]. This friction layer increases the real contact area and decreases friction, temperature and arcing.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…The presence of the commutator layer (up to a certain level of thickness) leads to a low coefficient of friction but simultaneously disturbs the current conduction through the brush and the commutator due to its relative high electrical resistance. Groth et al [8] investigated the transfer film using Microprobe analysis. In contrast to the previous investigations they concluded that the film is always very thin and contains mainly of MoS 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Generally, the brushes often require maintenance and need to be replaced after a certain period of time. However, new brushes have been recently introduced which last much longer than conventional brushes and require less maintenance [35], [36]. Furthermore, brushless topologies such as using sub-harmonic [37] or 3rd harmonic excitation [38] have also been introduced which do not need brushes and slip rings.…”
Section: Introductionmentioning
confidence: 99%